'Amethystus Princeps Sobrietatis': signing a sixteenth‐century pledge. Issue 1 (7th October 2011) - HERDMAN, EMMA
<x xml:space="preserve">Abstract</x> Against the backdrop of Montaigne's philosophical and ethical discussion of drunkenness, ecstasy and excess in 'De l'yvrongnerie', this article introduces the literary society founded in the 1570s by Johann Posthius and Paul Melissus in reaction to the licentiousness they perceived in Germany's long‐established drinking culture. Through analysis of the anthology of neo‐Latin verse that they consequently compiled, the Collegii Posthimelissaei Votum, their humanist society may be seen to have been founded out of a combination of religious, patriotic and vocational concerns. The significance of the Collegium's symbol, the amethyst, is examined in the light of the religious background to the vow – a background which is then balanced against the equal influences upon the Collegium of the satirical tradition surrounding Germany's drinking culture, and of the two founders' respective professions: medicine and poetry. Yet the anthology reveals that the Collegium was also motivated by more private concerns: the promotion of sober poetry both as a metaphorically purer form of wine and as a metonym for the friendship between sober poets that in itself resembles a form of ecstasy found in Montaigne.